DIGITAL TECHNOLOGY AND THE IMPORTANCE OF ARTIFICIAL INTELLIGENCE IN MEDICINE (Academia Science Repository, 2023)
The introduction of information technologies in the field of healthcare is one of the most important factors of today. Medical services provided by doctors to patients with modern methods of treatment, diagnostic methods, prevention of disease and restoration of health, increasing the speed of first aid provided to patients, effective use of digital technology and artificial intelligence, indicate the development of our medicine.